Selective H3 Antagonist (ABT-239) Differentially Modifies Cognitive Function Under the Impact of Restraint Stress - Trofimiuk, Emil; Wielgat, Przemysław; Car, Halina (Frontiers in Systems Neuroscience, 2021)
Background: A considerable number of competitive antagonists/inverse agonists of histamine H3 receptor (H3R) have progressed to clinical assessment, with pitolisant approved for the treatment of narcolepsy. H3R, highly expressed in the CNS, is regard as relevant target in CNS disorders. At the same time, new compounds including ABT-239 H3R antagonist (ABT; Benzonitrile, 4-[2-[2-[(2R)-2-methyl-1-pyrrolidinyl]ethyl]-5-benzofuranyl]-) are continually being tested. The aim of the study was to test ABT-239 as a prophylactic agent in stress-induced memory impairments. Methods: Stressed and non-stressed rats were pre-treated with ABT-239 and subsequently subjected to a number of behavioral tests aimed at assessing the animals' working and spatial reference memory (Morris water maze (MWM), Barnes maze (BM)), assessing the locomotor function and anxiety-like behaviour (Open field (OF), elevated ‘plus’ maze – EPM). Results: Chronically stressed rats displayed a significant decline in spatial (working and reference) memory. In the MWM test, we observed an improvement in spatial reference memory in stressed animals and a positive after ABT-239 pre-treatment. In the BM test, the effect of ABT-239 administration on spatial memory changed in successive attempts, from negative initially to favourable in subsequent attempts, and negative in the last trial of the test in the control group of rats. However, a beneficial effect is noted in the group of stressed animals, which remained throughout the entire testing period. Conclusions: Presented findings demonstrate that ABT-239 shows potential to abolish or prevent restraint stress-induced spatial memory impairments and cognitive deficits. However, in conditions of appetitive modulation, it could increase damage to memory (unstressed animals).